Aberrant expression of caspase 14 in salivary gland carcinomas. (25th September 2014) - Lemound, Juliana; Stucki‐Koch, Angelika; Stoetzer, Marcus; Kokemüller, Horst; Gellrich, Nils‐Claudius; Kreipe, Hans; Hussein, Kais
<x xml:space="preserve">Abstract</x> Objectives Caspase 14 is reduced in adenocarcinomas of the stomach and colon. In contrast, breast and lung adenocarcinomas frequently show an overexpression of caspase 14. Salivary gland adenocarcinomas have not been evaluated for potential aberrant caspase 14 expression. Materials and Methods Samples from salivary gland carcinomas (n = 43) were analysed by immunohistochemistry (caspase 14, filaggrin, GATA3 and Ki67) and fluorescence in situ hybridization. Results Caspase 14 is not expressed in normal salivary glands, while in a subfraction of carcinomas (32%) an aberrant expression was found. Filaggrin could not be detected. Caspase 14 staining was not associated with tumour dedifferentiation, GATA3 expression or amplification of gene locus 19p13. Conclusion In summary, aberrant expression of caspase 14 can be found in a subfraction of salivary gland carcinomas but could not be used as a biomarker for a specific carcinoma subtype of the salivary gland.